Nutritional strategies for a healthy transition to lactation: an update - Barry J. Bradford (Kansas Agricultural Experiment Station Research Reports, 2007)
Reducing cull rates and improving fertility in early lactation has a dramatic effect on the profitability of many dairies. Continuing research on transition cow nutrition has led to the development of an array of nutritional strategies to prevent disorders during the transition period. It is important, however, to realize that some of these strategies have similar modes of action, and as such, their effects are not likely to be additive. Producers should work with their nutritionist and veterinarian to identify the most prevalent transition problems in the herd and review options for preventing those disorders.; Dairy Day, 2007, Kansas State University, Manhattan, KS, 2007; Dairy Research, 2007 is known as Dairy Day, 2007
Keywords: Dairy Day; 2007; Kansas Agricultural Experiment Station contribution; no. 08-127-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 984; Dairy; Transition period; Monensin; Choline; Propylene glycol; Vitamin E